Usefulness of microbiological bile analysis in grade II cholecystitis according to the Tokyo classification (Revista Argentina de Cirugía, 2026)
Background: The Tokyo Guidelines 2018 for the Management of Cholecystitis (TG18) recommend intraoperative microbiological bile analysis (MBA) in moderate cases (grades II) to identify microorganisms and adjust antibiotic therapy.Objective: he aim of this study was to describe the results of samples obtained by intraoperative gallbladder aspiration for MBA and its association with comorbidities, PPI use, prior antibiotic therapy, and postoperative complications in patients with grade II cholecystitis.Material and methods: This observational, prospective and descriptive study included adult patients (> 18 years) diagnosed with grade II acute cholecystitis according to the TG18 managed with laparoscopic cholecystectomy (LC). Patients were assigned to two groups based on a positive or negative MBA. The data analyzed included demographic variables, medical history, and surgical and microbiological characteristics. The chi-square test (χ²) was used to compare categorical variables. A p-value < 0.05 was considered statistically significant.Results: Of the 272 patients who underwent LC, 51 had grade II acute cholecystitis; 29 (57%) were women, and mean age was 57 years (SD 18). The MBA was positive in 14 (27%) cases. Ten patients had a body mass index (BMI) of 25 or higher, 5 had comorbidities, and 7 used PPIs. None of the patients had received antibiotic therapy prior to hospitalization. E. coli was the most common germ involved (28%). All the germs were susceptible to ceftriaxone. There were no intraoperative adverse events resulting from gallbladder aspiration or postoperative complications.
Keywords: acute cholecystitis; bile infection; laparoscopic cholecystectomy; anti-bacterial agents; microbiology